An in situ bioassay for freshwater environments with the microalga Pseudokirchneriella subcapitata - Moreira-Santos, Matilde (2004)
This study was designed to evaluate the suitability of an in situ microalgal bioassay with Pseudokirchneriella subcapitata to be used in freshwater environments. The assay potential was investigated by deploying it in a system impacted by acid mine drainage. Water samples were collected to perform a laboratory assay also. P. subcapitata was viewed to be a good option for the in situ assay because it grew well and according to control acceptability criteria when immobilized in calcium alginate beads. A reduction in algal growth was apparent at both impacted sites demonstrating assay sensitivity: the site closest to the effluent discharge was clearly impacted and the one further downstream appeared to be moderately impacted. Results from the laboratory assay, designed to distinguish effects of nutrient differences across sites from those due to the effluent, confirmed the in situ responses. Results are discussed in light of the significance of combining information from different assessment tools, namely in situ and laboratory assays, as well as water-quality parameters, particularly at sites that are moderately impacted.